Computation and measurement of wind induced ventilation - Straw, Matthew Peter (2000)
This thesis aims to predict wind induced ventilation of a structure through the application of current analytical techniques, computational fluid dynamics simulations and novel techniques for ventilation flows induced by turbulent mechanisms. Validation of the predictions was carried out through full-scale measurements undertaken on a purpose built test structure. The structure was of cubic design with an external dimension of 6m. The construction of this full-scale research structure at Silsoe Research Institute, Bedfordshire, England, provided a unique opportunity for undertaking full-scale experimentation on a fundamental wind engineering test case which, prior to this thesis, had only been investigated using scale models in wind tunnels and computational simulations.